Automated Metabolic P System Placement in FPGA - Kulakovskis, Darius; Navakauskas, Dalius (Electrical, Control and Communication Engineering, 2016)
An original Very High Speed Integrated Circuit Hardware Description Language (VHDL) code generation tool that can be used to automate Metabolic P (MP) system implementation in hardware such as Field Programmable Gate Arrays (FPGA) is described. Unlike P systems, MP systems use a single membrane in their computations. Nevertheless, there are many biological processes that have been successfully modeled by MP systems in software. This is the first attempt to analyze MP system hardware implementations. Two different MP systems are investigated with the purpose of verifying the developed software: the model of glucose–insulin interactions in the Intravenous Glucose Tolerance Test (IVGTT), and the Non-Photochemical Quenching process. The implemented systems’ calculation accuracy and hardware resource usage are examined. It is found that code generation tool works adequately; however, a final decision has to be done by the developer because sometimes several implementation architecture alternatives have to be considered. As an archetypical example serves the IVGTT MP systems’ 21–23 bits FPGA implementation manifesting this in the Digital Signal Processor (DSP), slice, and 4-input LUT usage.